Consultancy Services Market for Micro, Small and Medium-Sized Enterprises in Croatia - Anamarija Delic; Mirela Alpeza (Economic Review: Journal of Economics and Business, 2017)
Business advisors and their impact on the perfor -mance of micro, small and medium-sized com- panies (MSMEs) have been in the focus of many researchers for a long time. MSMEs are reporting increasing interest in professional business advice, but only a small share of MSME owners is using consultancy services. This paper analyzes the con- sultancy market sector for MSMEs in Croatia, with a special focus on differences in the perspectives - gaps and overlaps of the supply (consultancy com- panies) and the demand side (MSME owners) of the market. The main objectives of the study are to identify and analyze determinants that influence consultancy market for MSMEs in Croatia, through opinions and views of the owners of MSMEs, on the one side, and consultants as service providers, on the other side (mirroring perspective). The empirical evidence in this paper is provid- ed through secondary research and primary re- search - a survey conducted among 303 MSME owners and 60 providers of consultancy services for MSMEs. The main findings of this study enable segmentation of the users of consultancy services for MSMEs and identification of market niche for MSME consultants. Based on the research results, recommendations for better understanding of MSME owners as clients of consultancy services are created, especially those related to improving marketing and service development strategies. The results of this study and the recommendations can be used by a wide network of advisory service providers for MSMEs (e.g. accountants, lawyers, IT consultants) for improving the quality of service and identification of market niches.
Keywords: L84; 330; Consultancy market services; Micro; small and medium-sized companies; Eentrepre- neurship supporting institutions